2014
DOI: 10.1002/cctc.201400040
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Effect of Brønsted Acidity of Supported MoOx Species on their Activity and Selectivity in Ethylene/trans‐2‐Butene Metathesis

Abstract: Supported catalysts with a nominal Mo surface density of 0.15 and 1.5 Mo atoms nm−2 were synthesized by impregnation of alumina, silica, and alumina–silica supports with silica content between 1 and 70 wt %. They were tested for their activity and selectivity in the metathesis of ethylene and trans‐2‐butene to propene between 343 and 603 K at 125 kPa. The catalysts were characterized by UV/Vis, Raman, and IR spectroscopy, XRD and H2 temperature‐programmed reduction for elucidating the distribution, degree of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 64 publications
(1 reference statement)
3
54
0
Order By: Relevance
“…Though the general route of carbene generation was clarified, the structural identification of the relevant surface molybdenum oxide precursor species remains an elusive challenge, as it demands discrimination of a small minority (≈1 %) from the majority of spectator species. As for alumina‐supported molybdenum oxide catalysts the nature of the precursor structure has been controversially discussed, favoring both monomeric, as well as oligomeric surface MoO x species. Here, we study correlations between surface density of molybdenum oxide species, acid‐base properties and catalytic properties taking a series of silica‐supported molybdenum oxide catalysts with different Mo loading as basis.…”
Section: Introductionmentioning
confidence: 99%
“…Though the general route of carbene generation was clarified, the structural identification of the relevant surface molybdenum oxide precursor species remains an elusive challenge, as it demands discrimination of a small minority (≈1 %) from the majority of spectator species. As for alumina‐supported molybdenum oxide catalysts the nature of the precursor structure has been controversially discussed, favoring both monomeric, as well as oligomeric surface MoO x species. Here, we study correlations between surface density of molybdenum oxide species, acid‐base properties and catalytic properties taking a series of silica‐supported molybdenum oxide catalysts with different Mo loading as basis.…”
Section: Introductionmentioning
confidence: 99%
“…Supports and catalysts were characterized by N 2 adsorption, ICP-OES, XRD, UV-vis and Raman spectroscopy, H 2 -TPR and IR pyridine adsorption. 8 The obtained results revealed that all catalysts with 0.15 Mo nm À2 possess highly dispersed tetrahedral MoO X species, while those with 1.5 Mo nm À2 contain polymerized octahedral MoO X . Catalytic tests were carried out in fixed-bed reactors at 423 K and 125 kPa.…”
mentioning
confidence: 83%
“…This may be related to higher Brønsted acidity of the former catalyst. 8 Another important difference between isolated tetrahedral and polymerized octahedral MoO X species is their ability to engage ethylene in propene formation. This conclusion was derived from analysing the reaction rates of propene formation (r Mo (propene)) and ethylene consumption (r Mo (ethylene)) in catalytic tests using reaction feeds with an ethylene/trans-2-butene ratio between 0.1 and 2.8.…”
Section: Upon Rising 2-butene Conversion Secondary Reactions Involvimentioning
confidence: 99%
See 1 more Smart Citation
“…Molybdenum oxide on silica, alumina or silica-alumina belongs to the well-known and long-time used metathesis catalysts [ 1 ]. Albeit typical ill-defined catalysts they are still popular as relatively cheap catalysts finding industrial applications especially in the treatment of low olefins [ 2 5 ]. Their catalytic activity depends on many factors, especially on Mo loading, support acidity, and pre-reaction activations.…”
Section: Introductionmentioning
confidence: 99%